Performance Implications Of Capital Budgeting Practices Of Private Waste Management Firms In Ghana. A Case Study Of Financial Zoomlion Ghana Limited - Mavis Amofah (2025)
This Research Work Could Not Have Been Achieved Without The Support Of Many Individuals. My Sincere Thanks Go To The Almighty God For Sustaining And Guiding Me Throughout This Work.I Would Like To Express My Appreciation To My Research Supervisor, Mr. Peter Avevor, For His Expert Advice, Useful Criticisms And Suggestions. Special Thanks To Ms. Blessing Amofah And Mr. Kofi Atta-Mensah For Their Support, Care And Encouragement Throughout This Course